Nursing assistance to the victim of a stroke in emergency: Integrative review (Research, Society and Development, 2025)
Objective: to describe the nursing assistance provided to a patient who is a victim of a stroke (CVA) during emergency care. Method: This is a literature review study, with a qualitative and descriptive approach, conducted in the databases BVS, BDENF, LILACS, MEDLINE, and SCIELO. The descriptors used were: "Cerebrovascular Accident": "Emergencies" "Nursing," covering the period from January 2013 to March 2023, in the languages English, Portuguese, and Spanish. Results: The research resulted in a total of 115 publications, which, after selection, resulted in 5 articles for the review. Nurses must identify the first signs and symptoms of a stroke as early as possible. In addition, it was observed that there is a deficiency in recognizing stroke symptoms in pre-hospital care. Final considerations: nursing assistance to the stroke patient in the emergency department occurs during the screening of healthcare units in recognizing stroke signs and symptoms early, for a better prognosis and to avoid neurological deficits in the individual.